2018
DOI: 10.1016/j.jinorgbio.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the role of a solvent tunnel in the α-ketoglutarate dependent oxygenase factor inhibiting HIF (FIH)

Abstract: Non-heme Fe(II)/α-ketoglutarate (αKG)-dependent oxygenases catalyze a wide array of reactions through coupling oxidative decarboxylation of αKG to substrate oxygenation. This class of enzymes follows a sequential mechanism in which O reacts only after binding primary substrate, raising questions over how protein structure tailors molecular access to the Fe(II) cofactor. The enzyme "factor inhibiting hypoxia inducible factor" (FIH) senses pO in human cells by hydroxylating the C-terminal transactivation domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…A detailed analysis is essential during the protein reengineering process. It can provide information about the residues blocking a potential new pathway, whose opening can promote significant modification of protein activity (52,67,68) or selectivity (23,29,69,70).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis is essential during the protein reengineering process. It can provide information about the residues blocking a potential new pathway, whose opening can promote significant modification of protein activity (52,67,68) or selectivity (23,29,69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding (M+αKG), the CTAD binding site shifts from low affinity (K D > 1 mM) to moderate affinity (K D = 80 μM), leading to a rigorously sequential binding order. 24 This has a practical effect, as there is but a narrow solvent accessible channel to the active site in the FIH/CTAD adduct, 14 which would prevent αKG from entering the active site were CTAD present. Otherwise, one could envision that CTAD binding to apoFIH might inhibit turnover by blocking αKG from reaching the active site.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast, average B-factors in the refined structures show that thermal fluctuations of FIH decrease upon binding (M+αKG), 11,12 and a mechanistic study further revealed that the access of O 2 to the active site was not limited by constriction in a narrow channel. 14 These kinetic and structural data suggest that protein dynamics may be essential for ligand binding in FIH, as seen for ligand binding in other metalloenzymes. [15][16][17] Establishing the connection between protein dynamics and substrate binding may provide insight into the sequential chemical mechanism as well as providing hints for selectively targeting members of this important enzyme superfamily.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…It is proposed that O 2 binds to an open coordination site on Fe­(II) (potentially induced by substrate binding as was precedented with other 2OG oxygenases , but notably not PHD2) yielding an Fe­(III) linked superoxide. The distal superoxide oxygen then attacks the C-2 carbonyl of 2OG, resulting in oxidative decarboxylation with formation of succinate, carbon dioxide (which likely efficiently leaves the active site), and a Fe­(IV)O intermediate, the latter of which is likely the active oxidant. ,, The ferryl species then stereospecifically abstracts a hydrogen atom from C-3 of HIF-α Asn803 to form a substrate radical and ferric hydroxide; a radical rebound process then gives the hydroxylated product and restores the Fe­(II) state. , The hydroxylated product and succinate are then released, , and the FIH-Fe­(II) complex can transition into a new catalytic cycle (Figure ).…”
Section: Mechanism Of Fih-catalyzed Protein Hydroxylationmentioning
confidence: 99%